2006
DOI: 10.1002/glia.20411
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 potentiates astrocytic nitric oxide production by expanding the population of astrocytes that express NOS‐2

Abstract: Both transforming growth factor-beta1 (TGF-beta1) and nitric oxide synthase-2 (NOS-2) are upregulated under various neuropathological states. Evidence suggests that TGF-beta1 can either attenuate or augment NOS-2 expression, with the prevailing effect dependent on the experimental paradigm employed and the cell-type under study. The purpose of the present study was to determine the effect of TGF-beta1 on astrocytic NOS-2 expression. In purified astrocyte cultures, TGF-beta1 alone did not induce NOS-2 or NO pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 106 publications
(138 reference statements)
2
68
0
Order By: Relevance
“…We demonstrated previously that treatment with TGF-β1 enhances astrocytic nitric oxide production induced by LPS plus interferon-γ (IFNγ) by increasing the number of astrocytes in a population that express NOS-2 [14]. To test whether TGF-β1 augments COX-2 expression in murine astrocytes, COX-2 mRNA and protein expression were examined in murine primary astrocyte cultures by qRT-PCR and Western blot analysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated previously that treatment with TGF-β1 enhances astrocytic nitric oxide production induced by LPS plus interferon-γ (IFNγ) by increasing the number of astrocytes in a population that express NOS-2 [14]. To test whether TGF-β1 augments COX-2 expression in murine astrocytes, COX-2 mRNA and protein expression were examined in murine primary astrocyte cultures by qRT-PCR and Western blot analysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Protein lysates were generated from cell cultures as previously described [14]. Protein concentrations were determined using the BCA Assay (Pierce).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…TGF-β1 is required for NF-kappaB-mediated modulation of iNOS activity when controlling the induction of the Epstein-Barr virus replication cycle [40] . A report showed that TGF-β1 stimulates NO production in astrocytes by recruiting distinct cell subpopulations [41] . Therefore, the iNOS expression induced by the TGF-β1/PI3K/Akt pathway may be a main reason for NO over-production in MCs cultured in high glucose ( Figure 6).…”
Section: Cell Proliferation In the Rat Mesangial Cellsmentioning
confidence: 99%
“…Reactive astrocytes can preserve neurons and oligodendrocytes, and protect motor functions after SCI (72,76,78), potentially due to the astrocyte-secretory polypeptides (astrocyte-derived cytokines and trophic factors), which alter the microenvironment (83)(84)(85). These cytokines include IL-1β, TNF-α, IL-6, IL-11 and transforming growth factor-β1 (86)(87)(88)(89)(90)(91)(92) and the trophic factors include brain-derived neurotrophic factor, glial cell line-derived neurotrophic factor, nerve growth factor (NGF), CNTF, basic fibroblast growth factor and leukemia inhibiting factor (LIF) (93)(94)(95)(96)(97). Recently, increasing evidence has indicated that cytokines and trophic factors secreted by reactive astrocytes may protect the injured tissues and cells through the JAK-STAT pathway (82,98).…”
Section: Astrocyte-secretory Polypeptides Promote Neuroprotection Viamentioning
confidence: 99%